Strengthening financial management systems at primary health care: Performance assessment of the Facility Financial Accounting and Reporting System (FFARS) in Tanzania - Ruhago, George M.; Ngalesoni, Frida N.; Kapologwe, Ntuli A.; Kengia, James T.; Ngocho, James; Kabusi, Stephen M.; Kalolo, Albino; Kitali, Erick J.; Rwamiago, Elisa; Mtei, Gemini (Frontiers in Health Services, 2023)
Background: Universal coverage remains a challenging pursuit all around the globe even among the most developed countries. Strengthening financial management capacity is essential towards attaining the three Universal Health Coverage (UHC) goals. In this regard, Tanzania introduced the Facility Financial Accounting and Reporting System (FFARS) in line with the introduction of the Direct Health Facility Financing (DHFF) initiative in Primary Health Care (PHC) in 2017/18. We aim to assess functionality of the FFARS in management, accounting, and reporting funds received and disbursed in the stride forward strengthening public financial management in primary health facilities towards UHC. Methods: The study applied implementation research using mixed method sequential explanatory design to assess the performance of the FFARS in more than 5000 PHC facilities in Tanzania. Quantitative methods assessed the changes in revenues and expenditure between the financial year (FY) 2017/18 and 2018/19 while the qualitative part explored the usability and the benefits FFARS offers in improving facility finances and reporting system. Data analysis involved thematic and descriptive analysis for qualitative and quantitative data respectively. Results: Out of the 5,473 PHC facilities, 88% were from rural based however; annual average revenue was higher in urban facilities in FY 2017/2018 and 2018/2019. Overall, district hospitals showed an increase whereas the health centers reported a decline of more than 40% in revenue. User fee was the predominant source of revenue particularly in urban facilities while revenue from health insurance was not among the top three highest sources of revenue. Expenditure priorities are more towards drugs and supplies (25%) followed by allowances and training (21%), these did not differ by facility geographies. In health centers, expenditure on facility infrastructure was predominant. Key Informant Interviews revealed an overall satisfaction and positive experiences related to the system. Conclusions: The implementation of FFARS in Tanzania demonstrated its high potential in improving facility financial management including its ability to track revenue and expenditure at PHC facilities. Staffing shortage, ICT infrastructure and limited opportunities for capacity building could be the limiting factors to reaching the potentials of FFARS implementation and attainment of its full impact on Tanzania’s pursuit for universal coverage.